The Politics of 'Exit': Emigration & Subject-Making Processes in Modern Egypt - Tsourapas, Gerasimos (Mashriq & mahjar, 2017)
How does emigration affect the politics of the country of origin? This paper argues that emigration is constitutive of subject-making processes within the sending state. Steering away from instrumentalist approaches that treat it as a prudential act, cross-border mobility is here examined as licensed political participation. By engaging in (or abstaining from) migration, citizens embed themselves deeper into specific social norms and practices as defined, discursively and substantively, by governmental policies. The act of migration, thus, allows citizens to infuse meaning into distinct social orders and engage in subject-making processes. The empirical case of modern Egypt demonstrates how such an approach can shed light upon the ways through which political structures are affected by emigration in non-democracies. In the divergent approaches to migration under President Nasser and, later, under Presidents Sadat and Mubarak, lie two different normative 'constructions' of the Egyptian subject: the frugal, self-sufficient Egyptian who rejects emigration under Nasser is contrasted with the self-interested, profit-seeking Egyptian subject-migrant under Sadat and Mubarak. By highlighting this opposition through the framework of cross-border mobility, this paper seeks to shed light into the multiple resonances that migration has as a subject-making process, and enhance our understanding of the politics of emigration under non-democratic regimes.